1999
DOI: 10.1034/j.1600-0420.1999.770304.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes of the human donor cornea during organ‐culture

Abstract: ABSTRACT.Purpose: To study metabolic changes of the human cornea during organ-culture. Morphological changes have been extensively studied, whereas changes in human corneal metabolism have not been investigated yet. Material and Methods: 106 human corneas were stored for 1, 7, 15, 18, 21 and 28 days in a closed-system under standard eyebank conditions. After storage, glucose, lactate, ATP, ADP and AMP concentrations were determined in each cornea. Results: Glucose concentration decreased during the first two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
1
19
1
2
Order By: Relevance
“…The most pronounced decrease in cell density was observed within the first week of cultivation irrespective of serum supplementation of the medium. A similar endothelial cell loss also occurs in medium MEM and seems to be related to adaptation to the artificial culture conditions [9].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The most pronounced decrease in cell density was observed within the first week of cultivation irrespective of serum supplementation of the medium. A similar endothelial cell loss also occurs in medium MEM and seems to be related to adaptation to the artificial culture conditions [9].…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of metabolic changes in organ-cultured donor corneas showed that the corneas recover during organ culture, especially during the first 2 weeks. Improved biochemical values were found during the first 4 weeks and acceptable conditions for only up to 6 weeks [8,9]. After 4 weeks of culture, the entire population of keratocytes was found to be still alive, but in contrast to the situation after 2 weeks only very few mitotic keratocytes could be detected [7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Dies konnte aufgrund einer geringeren Immunitat, wie z. B. Downregulierung von HLA-DR-Antigenen oder Auswandern von Langerhanszellen [1] oder aber aufgrund einer besseren Stoffwechsellage in Organkultur beruhen [22]. Eine weitere Moglichkeit ist eine bessere Kontrolle der Hornhautbank, da ja vor Transplantation nochmals die Qualitat einer Hornhaut gepruft wird and eventuelle schlechtere Transplantate noch ausgeschieden werden konnen and sich dadurch ein gewisser positiver Effekt durch gezieltere and verbesserte Transplantatauswahl ergibt, bzw.…”
Section: Spenderhornhkuteunclassified
“…Therefore, we recommend increasing the initial concentration to 5 mg/mL, the highest concentration found to be nontoxic to endothelial cells. 9 In Bern, where a medium change is performed for metabolic reasons at day 14 as suggested by Redbrake et al, 23 the amphotericin B concentration will exceed the highest MIC for Candida during the 14-day period of storage for both possible …”
Section: 10mentioning
confidence: 99%